Manual on postharvest handling of Mediterranean tree fruits and nuts - Crisosto, Carlos H.; Crisosto, Gayle M. (CABI, 2020)
This book provides valuable, up-to-date information on postharvest handling of seven fruit and nut crops: almond, fig, peach, persimmon, pistachio, pomegranate and table grape. These crops are of particular importance in the Mediterranean region and also to those countries that export and import these crops, in which intensive economic resources are dedicated to researching and solving their postharvest problems.